Find the error in this mathematical conundrum. Answer Saturday.

1=1 [To start]

a=b [Got it?]

a•a=b•a [Both sides multiplied by a]

a^2=ab [Which is]

a^2-b^2=ab-b^2 [Subtraction axiom with b^2]

(a+b)(a-b)=b(a-b) [Factored]

(a+b)(a-b)/(a-b)=b(a-b)/(a-b) [Divide both sides by (a-b)]

a+b=b [Which is]

b+b=b [Unnecessary step but shows the result easier]

2b=b [Which is]

2=1 [Equals]

## About James

This is a place to post things that I find interesting or puzzles and other things.

(a+b)(a-b)/(a-b)=b(a-b)/(a-b) [Divide both sides by (a-b)]

Lets fill this in knowing that x(any number but I chose 1)=a=b

(x+x)(x-x)/(x-x)=x(x-x)/(x-x)

Lets solve those parentheses and what do we have here!

(2x)

0/0=1(0/0)Anyone knows you cant divide by 0 (Even 0/0 as it causes some problems with logic) Making this incorrect and you now see where we get the 2x from.